2020
DOI: 10.1186/s13046-020-01772-y
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of VANGL1 by IGF2BPs and miR-29b-3p attenuates the detrimental effect of irradiation on lung adenocarcinoma

Abstract: Accumulating evidence suggests that radiation treatment causes an adaptive response of lung adenocarcinoma (LUAD), which in turn attenuates the lethal effect of the irradiation. Previous microarray assays manifested the change of gene expression profile after irradiation. Bioinformatics analysis of the significantly changed genes revealed that VANGL1 may notably influence the effect of radiation on LUAD. To determine the role of VANGL1, this study knocked down or overexpressed VANGL1 in LUAD. M6A level of VANG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…The most frequently observed histological subtype of lung cancer is non-small cell lung cancer (NSCLC), which is primarily classified into squamous cell carcinoma (LUSC) and adenocarcinoma (LUAD) [ 2 ]. Despite new developments in cancer therapeutic treatments for LUAD in recent years, including surgical resection, immunotherapy, chemotherapy and radiotherapy, the prognosis of LUAD continues to be frustrating, and its 5-year survival is less than 20% [ 3 ]. Therefore, there is an urgent need to identify robust biomarkers for predicting the prognosis of LUAD patients.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently observed histological subtype of lung cancer is non-small cell lung cancer (NSCLC), which is primarily classified into squamous cell carcinoma (LUSC) and adenocarcinoma (LUAD) [ 2 ]. Despite new developments in cancer therapeutic treatments for LUAD in recent years, including surgical resection, immunotherapy, chemotherapy and radiotherapy, the prognosis of LUAD continues to be frustrating, and its 5-year survival is less than 20% [ 3 ]. Therefore, there is an urgent need to identify robust biomarkers for predicting the prognosis of LUAD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) is the most common histological type of lung malignancies, accounting for over 80% of all cases, and near half of NSCLC are lung adenocarcinoma (LUAD) (3,4). The prognosis of LUAD has been disappointing over the past two decades, with a five-year survival rate below 20% (5). Mortality from LUAD has decreased substantially in recent years, coinciding with the advances in immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Sumo binding enzyme UBC9 regulates the SUMOylation of METTL3, controls homeostasis and promotes the accumulation of Snail, thus promotes the progression of HCC [ 105 ]. On the contrary, it is found that the expression of Snail mRNA decreases in the cells with SUMO mutant of METTL3 [ 106 ]. In addition, m6A can trigger the polysome mediated translation of Snail, which is in the CDS region of Snail instead of the 3’-UTR region, promote Snail transcription and participate in regulation EMT phenotype of tumor cells.…”
Section: The M6a and Transcription Factorsmentioning
confidence: 99%
“…The deletion of IGF2BP2/3 in m6A reader destroys the stability and expression of VANGL1 mRNA after radiation. Knockout VANGL1 can harm DNA from damage by activating BRAF-TP53BP1-Rad51 cascade, enhances the harmful effects of radiation on lung adenocarcinoma [ 106 ]. In cervical squamous cell carcinoma, FTO reduces β-catenin transcript, and promotes ERCC1 activity, thus enhancing chemo-radiotherapy resistance of cancer cells [ 162 ].…”
Section: Clinical Application Of M6a Methylation In Cancer Metabolismmentioning
confidence: 99%